The epileptology of Aicardi-Goutières syndrome: electro-clinical-radiological findings. (March 2021) - De Giorgis, Valentina; Varesio, Costanza; Viri, Maurizio; Giordano, Lucio; La Piana, Roberta; Tonduti, Davide; Roncarolo, Federico; Masnada, Silvia; Pichiecchio, Anna; Veggiotti, Pierangelo; Fazzi, Elisa; Orcesi, Simona; et al.
Highlights: Epilepsy in AGS is significantly related to the severity of brain calcification and the presence of startle reactions. Disruption of EEG organization is related to microcephaly and highly abnormal MRI signal intensity. EEG hallmarks are electrical organization disruption, focal slow and fast activity, and IEDs, regardless of the presence of seizures. Abstract: Objective: Although epileptic seizures occur in approximately a quarter of patients with Aicardi-Goutières syndrome (AGS), their phenotypic and electrophysiological characterization remains elusive. The aim of our study was to characterize epilepsy phenotypes and electroencephalographic (EEG) patterns in AGS and look for possible correlations with clinical, genetic and neuroradiological features. Methods: We selected patients with an established AGS diagnosis followed at three Italian reference centers. Medical records, EEGs and MRI/CT findings were reviewed. EEGs were independently and blindly reviewed by three board-certified pediatric epileptologists. Chi square and Fisher's exact tests were used to test associations between epilepsy and EEG feature categories and clinical, radiological and genetic variables. Results: Twenty-seven patients were enrolled. We reviewed 63 EEGs and at least one brain MRI scan per patient. Epilepsy, mainly in the form of epileptic spasms and focal seizures, was present in 37 % of the cohort; mean age at epilepsy onset was 9.5 months (range 1–36). The presence of epilepsy was associated with calcification severity (p = 0.016) and startle reactions (p = 0.05). Organization of EEG electrical activity appeared to be disrupted or markedly disrupted in 73 % of cases. Severe EEG disorganization correlated with microcephaly (p < 0.001) and highly abnormal MRI T2-weighted signal intensity in white matter (p = 0.022). Physiological organization of the EEG was found to be better preserved during sleep (87 %) than wakefulness (38 %). Focal slow activity was recorded in more than one third of cases. Fast activity, either diffuse or with frontal location, was more frequent in the awake state (78 %) than in sleep (50 %). Interictal epileptiform discharges (IEDs) were present in 33 % of awake and 45 % of sleep recordings. IEDs during sleep were associated with a higher risk of a epileptic seizures (p = 0.008). Significance: The hallmarks of EEG recordings in AGS were found to be: disruption of electrical organization, the presence of focal slow and fast activity, and the presence of IEDs, both in patients with and in those without epilepsy. The associations between epilepsy and calcification and between EEG pattern and the finding of a highly abnormal white matter T2 signal intensity suggest a common anatomical correlate. However, the complex anatomical-electroclinical basis of AGS-related epilepsy still requires further elucidation.